The Prosecution Laws - Shabbir Hussain Gigyani; Shabbir Hussain Gigyani (Lahore Farooq Printers, 2017)
Punjab criminal prosecution Service Constitution function and powers 2 Punjab Criminal Prosecution Service conditions of service service, 3 the Public Prosecution Directorate General Inspection Service Rule 2011
Punjab criminal prosecution Service Constitution function and powers 2 Punjab Criminal Prosecution Service conditions of service service, 3 the Public Prosecution Directorate General Inspection Service Rule 2011
Keywords: Punjab criminal prosecution Service Constitution function and powers 2 Punjab Criminal Prosecution Service conditions of service service, 3 the Public Prosecution Directorate General Inspection Service Rule 2011